PENGARUH DUKUNGAN ORGANISASI DAN KEPRIBADIAN TERHADAP KEPUASAN KERJA DENGAN STRES KERJA SEBAGAI MEDIASI (STUDI PADA PT.NUSPRO TELEMEDIA PERSADA KABUPATEN REMBANG) - Eli Pusriyanto, 1352020077; Rijanti, Tristiana (Jurnal Mahasiswa Pasca Sarjana, 2015)
The success of an organization is influenced by support organizations, every organization is always trying to improve support for employees to realize the vision and mission so that the goals of the organization would be a good reached. Personality will reduce employee stress and will improve employee job satisfaction in working be organized. Research aims to analyze the influence organizational support and personality to job satisfaction with job stress as mediation in PT.Nuspro Telemedia Persada District Rembang. Samples this study are employees of Telemedia Persada PT.Nusapro Rembang who has worked for 5 years or more of 120 people / respondents. Based on the results of the analysis showed that the variables of organizational support, personality, work stress partially or simultaneously positive effect on employee job satisfaction PT.Nusapro Telemedia Persada District Rembang in carrying out its duties and responsibilities. Based on work stress variable path analysis is not a mediating variable organizational support and personality to job satisfaction and organizational support for variable direct personality stronger influence on job satisfaction. Keywords: Organizational Support, Personality, Job Stress and Job Satisfaction